THE CLINICAL SIGNIFICANCE OF SERUM HAPTOGLOBIN IN EAR, NOSE AND THROAT DISEASES - KATAURA, Akikatsu; MORIMOTO, Kenji; ENOMOTO, Kazuko; DOI, Yasuyuki (JIBI INKOKA TEMBO, 1977)
Heptoglobin (Hp) is a glycoprotein in the α2-globulin fraction, which has a specific affinity for binding with Hb. The biochemical, biological and pathological significance of its affinity to Hb has been studied in 252 subjects consisting of patients with cancer, malignant lymphoma, or inflammatory diseases of the ear, nose and throat. Serum haptoglobin level of the cancer patients is found to be higher than that of normal individual, and roughly parallels the serum seromucoid level. Also, it was found that the serum haptoglobin level in acute inflammation is the highest among the various diseases. It was felt that the qualitative measurement of serum haptoblobin values is quite valuable not only as a supplement for diagnosis of malignant neoplasmas but also for diganosis of acute reactionary phase of inflammation.